ETRASIMOD IN THE TREATMENT OF ULCERATIVE COLITIS: EFFICACY, SAFETY, AND ITS ROLE IN THERAPY - REVIEW - Patrycja Kardasz; Aleksandra Piech; Martyna Grodzińska; Tomasz Ufniarski; Maria Ufniarska; Karol Poplicha; Justyna Moszkowicz; Piotr Sobkiewicz; Karolina Pasierb; Bartłomiej Siuzdak; Marta Jutrzenka; Patrycja Ucieklak (International Journal of Innovative Technologies in Social Science, 2025)
Ulcerative colitis (UC) is a chronic inflammatory disease of the large intestine, often associated with significant impacts on patients' quality of life and public health systems. Traditional treatments, such as aminosalicylates, are not always effective, especially in moderate to severe cases. Etrasimod, a novel oral selective modulator of sphingosine-1-phosphate (S1P) receptors, offers an innovative therapeutic approach by regulating immune cell migration and reducing intestinal inflammation. This review explores the efficacy, safety, and potential role of Etrasimod in the treatment of UC. Recent clinical trials have demonstrated its significant effectiveness in both the induction and maintenance of remission in patients with moderately to severely active UC. The drug also shows a favorable safety and tolerability profile. These findings position Etrasimod as a promising alternative for patients who do not respond to standard therapies. As research progresses, Etrasimod may represent a step forward in the development of more targeted, disease-modifying treatments for ulcerative colitis. Aim of the study: This review investigates Etrasimod’s role in ulcerative colitis treatment, in particular focusing on its mechanism of action, clinical efficacy, and safety. It seeks to determine whether it could serve as an alternative for patients resistant to conventional treatments. Methodology: A literature review was conducted using PubMed, Google Scholar, and clinical trial registries. Summary: Ulcerative colitis treatment remains challenging, with many patients experiencing limited benefits from existing therapies. Etrasimod, a selective modulator targeting S1P receptors, has demonstrated efficacy in induction and maintenance therapy in patients with moderately to severely active ulcerative colitis. Findings from clinical trials, particularly ELEVATE UC 12, 40 JAPAN and 52, suggest its potential in ulcerative colitis treatment. Further long-term studies are needed to confirm its benefits.